2016
DOI: 10.1111/liv.13045
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Hong Kong Liver Cancer Staging System in Europe

Abstract: The BCLC staging system performs better for European patients than the HKLC staging system in predicting OS. Twice more patients are eligible for a curative therapy with the HKLC algorithm; whether this translates in survival benefit remains to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…We have read with interest the article by Kolly et al (1) regarding the performance of BCLC and HKLC systems to assess HCC prognosis. They conclude that BCLC is better for HCC prognostic assessment.…”
mentioning
confidence: 96%
“…We have read with interest the article by Kolly et al (1) regarding the performance of BCLC and HKLC systems to assess HCC prognosis. They conclude that BCLC is better for HCC prognostic assessment.…”
mentioning
confidence: 96%
“…Studies suggest that the BCLC system can predict prognosis more accurately for Caucasian HCC patients than Asian ones, while the converse may be true of the HKLC system [811]. Though both staging systems are comprehensive, many patients do not fall neatly into their pre-specified treatment pathways [11], and even patients within the same BCLC or HKLC stage can differ substantially.…”
Section: Discussionmentioning
confidence: 99%
“…Studies based on Western population found the BCLC system can predict overall survival and/or disease-free survival more accurately for Western patients with HCC than Eastern ones. However, studies based on Estern population found HKLC or China liver cancer (2017 Edition) staging system is better than Western ones [15,16] . Therefore, selection of stage system should be based on population characteristics.…”
Section: Should Postoperative Hcc Patients Receive Adjuvant Treatmmentioning
confidence: 94%